Bodily self-recognition and body size overestimation in restrictive anorexia nervosa: implicit and explicit mechanisms - Ambrosecchia, Marianna; Ardizzi, Martina; Russo, Elisa Caterina; Ditaranto, Francesca; Speciale, Maurizio; Vinai, Piergiuseppe; Todisco, Patrizia; Maestro, Sandra; Gallese, Vittorio (Frontiers in Psychology, 2023)
It is widely known that among others, a pervasive symptom characterizing Anorexia nervosa (AN) concerns body-image overestimation, which largely contribute to the onset and maintenance of Eating Disorders. In the present study, we investigated the nature of the body image distortion by recording accuracy and reaction times in both a group of healthy controls and AN patients during two validated tasks requiring an implicit or explicit recognition of self/other hands stimuli, in which the perceived size of the stimuli was manipulated. Our results showed that 1) the perceived size of hands stimuli modulated both the implicit and explicit processing of body parts in both groups; 2) the implicit self-advantage emerged in both groups, but the bodily self, at an explicit level (perceptual, psycho-affective, cognitive) together with the integration and the distinction between self and other, was altered only in restrictive anorexia patients. Although further investigations will be necessary, these findings shed new light onto the relationship between the different layers of self-experience and bodily self-disorders.